2018
DOI: 10.1017/ice.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Single Xpert MTB/RIF Assay to Determine the Duration of Airborne Isolation in Hospitalized Patients With Suspected Pulmonary Tuberculosis

Abstract: BACKGROUNDHospitalized patients with suspected tuberculosis (TB) are placed in airborne isolation until 3 sputum smear samples are negative for acid-fast bacilli (AFB). The Xpert MTB/RIF assay ("Xpert") nucleic acid amplification test (NAAT) to identify Mycobacterium tuberculosis DNA and resistance to rifampicin is superior to AFB sputum smear microscopy for the diagnosis of TB.OBJECTIVETo compare the performance of a single Xpert to AFB smear microscopy for time to airborne infection isolation (AII) discontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Discontinuation of respiratory isolation based on the molecular test would reduce hospital expenditures and facilitate the reallocation of resources in deficient areas without compromising occupational risk. 16 Although theoretical, our model represents real scenarios of clinical practice and demonstrates, as have other studies such as Chaisson et al 8 and Poonwala et al, 14 a high single GeneXpert MTB/RIF NPV (ie, 99% in both studies) that is even higher than the NPV of sequential AFB smears. In our study, in group 3, a single GeneXpert MTB/RIF showed performance similar to that of 3 AFB smears, but in a shorter period.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Discontinuation of respiratory isolation based on the molecular test would reduce hospital expenditures and facilitate the reallocation of resources in deficient areas without compromising occupational risk. 16 Although theoretical, our model represents real scenarios of clinical practice and demonstrates, as have other studies such as Chaisson et al 8 and Poonwala et al, 14 a high single GeneXpert MTB/RIF NPV (ie, 99% in both studies) that is even higher than the NPV of sequential AFB smears. In our study, in group 3, a single GeneXpert MTB/RIF showed performance similar to that of 3 AFB smears, but in a shorter period.…”
Section: Discussionsupporting
confidence: 68%
“…12,13 Recent studies have demonstrated the possibility of using only 1 GeneXpert MTB/RIF to determine the continuation of respiratory isolation because performing >1 molecular test did not produce a superior result. 8,14,15 The economic importance of early patient removal from isolation beds has also been emphasized. 16 Cowan et al 13 estimated a shorter median of hospitalization in airborne isolation with the single GeneXpert MTB/RIF strategy, which would result in a cost savings of up to US$11,466 per patient compared to AFB smear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a positive correlation of Xpert and Ultra semiquantitative results was found with the smear microscopy results, which could guide airborne isolation measures. This could reduce the time to isolation in emergency services in low-prevalence setting (1, 3, 4). In our institution, we consider patients with negative Ultra results to be likely to be smear negative.…”
Section: Discussionmentioning
confidence: 99%
“…Xpert displays reduced turnaround time and shortened patient isolation and time to initiate anti-TB drugs and is more sensitive and specific than smear microscopy for acid-fast bacillus (AFB) detection. This test is now recommended to initiate the microbial diagnosis of tuberculosis (13), as well as to address patient’s transmission potential based on the semiquantitative result (1, 4, 5). Despite a very low limit of detection (LOD; ∼131 CFU/ml), Xpert remains less sensitive than liquid culture (LOD ∼1 to 50 CFU/ml) (6).…”
Section: Introductionmentioning
confidence: 99%